Effect of Particle Size of Sawdust on Behaviour of Sawdust/UPE Composites in Water - Ali, Nisreen S.; Fahad, Besma M. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The aim of the present work is to develop a new class of natural fillers based polymer composites with sawdust (S.D) which used two particle sizes (1.2 μm & 2.3 μm) and different weight percentage from sawdust (10%, 15%, and 20%). The mechanical properties studied include hardness (shore D) for all samples at normal conditions (N.C). The unsaturated polyester (UPE) and its composites samples were immersed in water for  30 days to find the effect of particle size of sawdust (S.D) on the weight gain (Mt %) by water for all the samples, also to find the effect of water on their hardness. The results show that the composite materials of sawdust (S.D) fillers which has particle size (1.2 μm) better than (2.3 μm) particle size before & after the immersion in water. Also the results show a decrease in the values of the hardness for the UPE and its composites samples after immersion in water. The results show that the UPE and its composites samples have relatively increased values of weight gain (Mt %) by water with time of immersion, for sawdust composite samples (1.2 μm) particle size the samples of (15%) weight percentage have relatively highest values of weight gain (Mt %) by water but for samples of (2.3 μm) particle size the samples of (20 %) weight percentage have relatively highest values of weight gain (Mt %). Finally results show that the value of weight gain (Mt %) increased with increasing of particle size of sawdust so that the composites samples have highest value of weight gain (Mt %) than UPE sample.